Analisis Kemampuan Berpikir Kritis Siswa Pokok Bahasan Klasifikasi Materi dan Perubahannya - Shofwan Ridho; Ruwiyatun Ruwiyatun; Bambang Subali; Putut Marwoto (Jurnal Penelitian Pendidikan IPA, 2020)
Abstract: This study aims to analyze students' critical thinking skills in science education on the subject matter of classification of material and its changes. This study included quantitative descriptive research. The subjects of this study were the eighth-grade students of MTs Wahid Hasyim Warungasem, Batang with a total of 27 students. The technique of collecting data uses the questions of critical thinking skills which number ten questions. The results showed that critical thinking skills in the basic explanatory aspects were 31% (low category), building basic skills by 61% (medium category), concluded by 17% (very low category), making further explanations of 46% (medium category), and strategy and technique of 20% (very low). Thus, the average critical thinking ability of students as a whole is in the low category with an achievement percentage of 35.2%. Key Words: Analysis of Critical Thinking; Science Education; Material Classification